Perpustakaan sebagai Teropong Profesionalisme Pustakawan - Aris Nurohman (Institut Agama Islam Negeri (IAIN) Curup, 2018)
Library is an institution that can not be separated from the role of librarians. Library dependence to the librarian is seen almost in the whole library complexity. Starting from planning, organizing, leadership, and control. Through this writing the authors will contribute a more real attachment between librarians and libraries. Based on some literature proves that between librarian and library can not stand alone. Starting from the management, service products and aspects of library accreditation assessment, librarians are instrumental in contributing enormously. Because of this dependence illustrates that the quality of the library will be seen from the quality of the librarian profession.